Níveis de lisina e de metionina+cistina para coelhos da raça Nova Zelândia Branco em crescimento - Motta, Ana Carolina Monteiro (2011)
Four experiments, two assays on nitrogen balance (NB) and two assays on growth, were undertaken to analyze the effect of different levels of Lysine and Methionine+Cystine (Lys and Met+Cys) on 31-50 and 51-70-day-old rabbits. For each NB assay, 75 animals were allotted to a 5 x 3 randomized design (five levels of Lys: 0.55; 0.65; 0.75; 0.85 and 0.95% versus three levels of Met+Cys: 0.5; 0.6 and 0.7%), with 15 treatments of five repetitions. Each assay lasted 14 days, comprising 10 days of adaptation and four days for feces and urine collection. Further, 180 rabbits aging 31-50 and 51-70 days were evaluated for growth, featuring randomized blocks and factorial scheme with the same diets as those of the previous assay, with a total of 15 treatments of 12 repetitions, and one animal for each experimental unit. Quadratic effects of increasing levels of Met+Cys on the nitrogen excreted in the urine (UN) for the 31-50-day-old rabbits were noticed. In fact, the lowest excretion occurred when the diet consisted of 0.59% Met+Cys. Increasing levels of Lys influenced the UN and the nitrogen retained daily (RN), the lowest UN when the diet consisted of 0.728% Lys and the maximal RN when it consisted of 0.724% Lys. Increases in the dietary levels of Met+Cys failed to affect either the performance of the rabbits up to 50 days old or the characteristics of the carcass. On the other hand, live weight of 50-day-old animals, daily weight gain, and food conversion up to 50 days of rabbits killed at that age showed a quadratic effect in proportion to the increasing levels of Lys. The best results were obtained at diet levels of 0.75, 0.738, 0.736% Lys, respectively. As for the 51-70-day-old rabbits, quadratic effects of increasing Met+Cys levels on the UN were recorded, with the lowest UN when the diet consisted of 0.603% Met+Cys, and of increasing levels of Lys on the UN and RN, with the lowest UN with the diet consisted of 0.602% Lys and the maximal RN when the diet consisted of 0.723% Lys, respectively. As for the growth assay, quadratic effects were found only for increasing levels of Lys for live weight at 70 days, weight gain and food conversion in 51-70-day-old rabbits, with the best results when the diet consisted of 0.740, 0.732, 0.734% Lys, respectively. The results show that the most adequate Lys and Met+Cys levels for 31-50-day-old rabbits were 0.75% and 0.5% and for 51-70-day-old rabbits 0.74% and 0.5%, respectively.